The sociopragmatic study of speech acts in Goet Ira in the Wee Mbaru cultural rite - Daar, Gabriel Fredi (Universitas Syiah Kuala, 2023)
Wee Mbaru is a cultural rite of entering a new house in the Manggarai speech community speaking the Pasat-Ruis dialect in Flores Island, East Nusa Tenggara Province, Indonesia. Ira is one of the phases in this cultural tradition. At this stage, a Tongka (spokesperson) and participant representatives conduct cultural interactions using goet (expression or proverb). This study aimed to analyze the speech acts of goet in the Ira phase. The study used a qualitative method with a phenomenological approach. Data were collected using in-depth interviews with seven key informants, taken purposively with the main criteria of having adequate knowledge of Manggarai culture, good ability to use goet, and experience as a Tongka. The results showed that the speech acts of goet in the Ira phase included representative and directive acts (illocutionary acts). The study also found that the expressive speech act of gratitude, prayers, and hopes, and the speech act of giving financial support are categorized as perlocutionary speech acts. The use of goet by a Tongka and participant representatives is considered a language politeness strategy effective for refining the language used, especially for avoiding face-threatening acts. Tongka and participant representatives need to understand the context and situation of the speech so that the choice of goet is appropriate and conveyed judiciously.